AN EMPIRICAL EXAMINATION OF THE RELATIONSHIP BETWEEN CORPORATE SOCIAL RESPONSIBILITY AND PROFITABILITY. - Aupperle, K. E.; Carroll, A. B.; Hatfield, J. D. (Academy of Management Journal, 1985)
Although there has been considerable research into the relationship between corporate social responsibility and profitability, it has frequently reflected either an ideological bias or limited meth...